1997
DOI: 10.1111/j.1439-0442.1997.tb01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diets with Graded Levels of Naturally Deoxynivalenol‐contaminated Oats on Immune Response in Growing Pigs

Abstract: Summary A trial was conducted to evaluate the effect of including different levels of deoxynivalenol (DON)‐contaminated oats in the complete diets of growing pigs on immune response and performance. The diets contained 0.6, 1.8 and 4.7 mg DON/kg, and both restricted and ad libitum feeding were used. Performance was recorded as weight gain, feed intake, efficiency of feed utilization and carcass quality. Immune response parameters recorded included primary and secondary antibody titres after injections of five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…The fact that DON had no effect on the immune response to vaccination is in accordance with the studies of Rotter et al. (1994), Overnes et al. (1997), Swamy et al.…”
Section: Discussionsupporting
confidence: 90%
“…The fact that DON had no effect on the immune response to vaccination is in accordance with the studies of Rotter et al. (1994), Overnes et al. (1997), Swamy et al.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, Bergsjø et al (1993) assessed a significant reduction of feed utilization in fattening pigs (21.3-100 kg) after feeding a diet containing 3.5 mg DON/kg ad libitum. Other studies (Rotter et al, 1994;Swamy et al, 2003;Øvernes et al, 1997) even revealed an increase in feed efficiency, and supposed that pigs adjusted to reduced feed intake by improving feed utilization. However, Da¨nicke et al (2004a) inferred no significant effects on performance when fattening pigs were fed with increasing DON concentration (0.2, 0.7, 1.2, 2.5 and 3.7 mg/kg) from wheat inoculated artificially with Fusarium culmorum.…”
Section: Growth Experimentsmentioning
confidence: 98%
“…Feeding trials where naturally or artificially infected material has been mixed into the diet show decreased feed consumption and weight gain in pigs already at doses from 0.6 -2 mg DON/kg feed Overnes et al, 1997;Bergsjö et al, 1993bYoung et al, 1983. The consumption of DON-contaminated feed has been associated also with epithelial lesions in the oesophageal region of the stomach when pigs have been given naturally infected feed containing from about 3 -6 mg DON/kg feed Foster et al, 1986;Friend et al, 1986bRotter et al, 1992, 1995.…”
Section: Toxic Effects In Pigsmentioning
confidence: 99%